Nursery practices in oil palm a manual - Laksono, Nur Dian (Techniques in plantation science series., 2019)
This is a practical guide which general and specific practices in oil palm nurseries to produce healthy, vigorous and uniform plants ready for field planting. Oil palm is the world's top oil crop